STUDENTS' MATHEMATICAL REASONING ABILITY ON THE CIRCLE CONCEPT - Anderson Leonardo Palinussa; Thobita Dias (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The condition of the Covid-19 pandemic that hit Indonesia, requires students and teachers to study from home in order to maintain their safety and health. However, entering the new normal era, people and even schools have started to carry out their usual activities while still paying attention to health protocols. Even though the learning process is still carried out online and offline, it is a challenge in learning mathematics. The purpose of this study is to analyze the mathematical reasoning abilities of students who take part in online and offline learning and to describe the attitudes of students who take online and offline learning towards learning mathematics in circle material. This research is an experimental research with the research instruments used are tests of mathematical reasoning abilities and questionnaires for implementing online and offline learning. This research was conducted on students of grade 11 science at SMA Negeri 14 Central Maluku. Based on the results of the study it was found that the mathematical reasoning abilities of students who received online and offline learning were more effective in the experimental class with the Inquiry-Discovery model compared to the control class. Thus learning using online and offline is suitable to be applied in learning mathematics, because students seem more active in solving the questions given by the teacher.Kondisi pandemi covid-19 yang melanda Indonesia, mengharuskan siswa maupun guru belajar dari rumah demi menjaga keselamatan dan kesehatan mereka. Namun memasuki era new normal, masyarakat bahkan di sekolah-sekolah sudah mulai melakukan aktivitas seperti biasa dengan tetap memperhatikan protokol kesehatan. Walaupun dalam proses pembelajaran masih dilakukan dengan daring dan luring, sehingga merupakan tantangan dalam pembelajaran matematika. Adapun tujuan dari penelitian ini adalah untuk menganalisis kemampuan penalaran matematis siswa yang mengikuti pembelajaran daring dan luring dan untuk mendeskripsikan sikap siswa yang mengikuti pembelajaran daring dan luring terhadap pembelajaran matematika pada materi lingkaran. Penelitian ini merupakan penelitian eksperimen dengan instrumen penelitan yang digunakan adalah tes kemampuan penalaran matematis dan angket pelaksanaan pembelajaran daring dan luring. Penelitian ini dilakukan pada siswa kelas 11 IPA pada SMA Negeri 14 Maluku Tengah. Berdasarkan hasil penelitian ditemukan bahwa kemampuan penalaran matematis siswa yang memperoleh pembelajaran dengan daring dan luring lebih efektif pada kelas eksperimen dengan model Inquiry-Discovery dibandingkan dengan kelas kontrol. Dengan demikian pembelajaran dengan menggunakan daring dan luring cocok diterapkan dalam pembelajaran matematika, karena siswa terlihat lebih aktif dalam menyelesaikan soal-soal yang diberikan oleh guru.